2022
DOI: 10.3390/su14116839
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Recycled Plastic Waste in Fiber Reinforced Concrete for Eco-Friendly Footpath and Pavement Applications

Abstract: The use of concrete in road construction has grown over the past decade due to the material’s great durability. However, concrete has poor tensile strength, ductility, and energy absorption. This paper aims to investigate the utilization of plastic waste, namely polypropylene (PP), to create a novel fiber to enhance the engineering properties of fiber reinforced concrete (FRC), an eco-friendly concrete that can reduce environmental problems. The 28-day design strengths of 28 and 32 MPa were used in this study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…This is accompanied by the high content of voids in previous concrete which also reduces its compressive strength. Similar findings were recorded in the literature [18], [31], [32].…”
Section: Compressive Strengthsupporting
confidence: 92%
“…This is accompanied by the high content of voids in previous concrete which also reduces its compressive strength. Similar findings were recorded in the literature [18], [31], [32].…”
Section: Compressive Strengthsupporting
confidence: 92%
“…Small RCA-FAG samples were collected from the center and their scanning electron microscope (SEM) analysis was assessed [43,44]. For FA contents more than 20%, the maximum dry unit weight of RCA-FAG samples dropped due to FA's lower specific gravity [18,19]. height of 116.4 mm.…”
Section: Sample Preparation and Testingmentioning
confidence: 99%
“…They reported that RCA needs to be improved by a binder (cement, lime, and fly ash) due to low physical properties (high water absorption and porosity) and engineering properties (low strengths) [11][12][13]. Nonetheless, cement manufacturing emits huge quantities of carbon dioxide (CO 2 ) into the atmosphere [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Waste materials including electric arc furnace (EAF) ladle furnace (LF) slags, coal fly (CF) ash, bottom ash, glass waste (GW) and reclaimed asphalt pavement (RAP) were used to improve the economic and environmental sustainability of road constructions [7]. Carbon reduction in pavement construction was observed when recycled plastic (RP) waste was used at varying proportions to enhance the engineering properties for eco-friendly pavement application [8]. Road pavements are superimposed layers of materials placed over the natural ground [9,10].…”
Section: Introductionmentioning
confidence: 99%